Предмет: Алгебра,
автор: zykova2002zykov
Помогиииитеееее!!!!!!!!
Приложения:
Ответы
Автор ответа:
0
а) (с+2)(с-3)-(с+1)(с+3)=
с(в квадрате)+3с+2с-6-с(в квадрате)-3с-с-3=2с-6-с-3
б)(4х-3)(в квадрате)-6х(4-х)=4х(в квадрате)-24х+3(в квадрате)-24х-6х(в квадрате)=-2х(в квадрате)-48х+3(в квадрате)=-50х(в квадрате)+3(в квадрате)
в)b(в квадрате)-9+(2b+3)(в квадрате)=b(в квадрате)-9+4b+12b+9=b(в квадрате)+16b
с(в квадрате)+3с+2с-6-с(в квадрате)-3с-с-3=2с-6-с-3
б)(4х-3)(в квадрате)-6х(4-х)=4х(в квадрате)-24х+3(в квадрате)-24х-6х(в квадрате)=-2х(в квадрате)-48х+3(в квадрате)=-50х(в квадрате)+3(в квадрате)
в)b(в квадрате)-9+(2b+3)(в квадрате)=b(в квадрате)-9+4b+12b+9=b(в квадрате)+16b
Похожие вопросы
Предмет: Английский язык,
автор: dzagnwipl12334
Предмет: Химия,
автор: ababinov965
Предмет: Английский язык,
автор: Аноним
Предмет: Математика,
автор: Ксения4566
Предмет: Математика,
автор: Niko5